Forest and shrubland structure of Polylepis tarapacana in topographic and substrate gradients across the Argentine Altiplano - Lopez, Victoria Lien (2025)
Background: Polylepis tarapacana (queñoa) is a species that grow from forests to shrublands in Chile, Argentina, Bolivia and Peru, reaching an elevation range of 4400-5000 m a.s.l. In Argentina, this species occurred in the Altoandina phyto-geographic eco-region, which presents scarce vegetation, and where it is the most important tree species for its great socio-economic importance. The structure of these communities and the changes related to environmental gradients are not well described in the literature. The objective was to relate topographic factors with variables of structure of the P. tarapacana communities, evaluating the occupation degree (e.g. density and crown cover) of the species. Methods: We studied P. tarapacana forests and shrublands in northern Argentina, sampling 98 plots (50–4000 m²) to measure diameter at the base (DAB-cm), dominant height (DH-cm), life forms, crown cover (CC-%), and density (DEN-n ha-1). Topographic variables (elevation, slope, aspect) and substrate type were also recorded. Generalized Linear Models (GLM) were used to assess the influence of topography on forest structure, and univariate analyses to evaluate structural changes across life forms with topography. Results: Great heterogeneity was observed in the structure of open forests or shrublands patches of P. tarapacana, at high elevations (<4500 m a.s.l.), gentle slopes (21°) and in north aspect (95% of the plots). Topographic factors influence vegetation structure variables, e.g: elevation has a significant positive effect on DH (β = 0.105, p = 0.011), while slope (β = -0.144, p = 0.001) and eastern aspect (β = -0.083, p = 0.040) have significant negative effects on DH (F=6.85, p <0.001). Slope was the only significant variable with a positive effect on CC (β = 0.275, p = 0.001). The life forms of P. tarapacana are influenced by topographic gradients, and the tallest communities (178.2 cm DH) are found at high elevations and low slopes, mainly in areas with bare soil and understorey vegetation. Conclusions: Polylepis tarapacana structure was associated to the studied topographic gradients. It is crucial to identify changes in the composition and structure of forest and shrubland, considering both the substrate in which they develop, and the different life forms they adopt.